(untitled) - Hilton, Ronald W. (Boston, Mass., 2003)
Hilton/Maher/Selto (HMS) addresses traditional cost concepts, but makes cost accounting functional by focusing on measuring and managing costs. HMS maintains that, Costs don't just happen, and with a pro-active approach toward costs, accountants can add value to an organization. Faculty will appreciate the new and more conventional chapter organization in the first two sections of the text. The real-world approach of this text, including the use of focus companies and the new accompanying focus sites, provides a realistic business environment, and aids in student comprehension and interest in the subject.
Keywords: Cost accounting,Managerial accounting